BIOM-30. BLOOD COUNTS THROUGH TREATMENT COURSE IN NEWLY DIAGNOSED GLIOBLASTOMA PATIENTS RECEIVING CHEMORADIATION. (12th November 2021) - Deng, Davy; Hammoudeh, Lubna; Cagney, Daniel; McFaline-Figueroa, J Ricardo; Chukwueke, Ugonma; Reardon, David; Lee, Eudocia Quant; Nayak, Lakshmi; Lim-Fat, Mary Jane; Ligon, Keith; Bi, Wenya Linda; Arnaout, Omar; et al.
Abstract: BACKGROUND: Glioblastoma (GBM) patients are treated with radiation therapy (RT), temozolomide, and corticosteroids which can affect hematologic and immunologic parameters. We examined lymphocytes, neutrophil-to-lymphocyte ratio and platelet measurements and their association with progression-free survival (PFS) overall survival (OS). METHODS: We identified 759 newly diagnosed adult GBM patients treated at our institution in the temozolomide (TMZ) era with blood counts that could be automatically extracted from the electronic medical record during chemoradiation (CRT, defined as within 42 days of RT) and at first recurrence. Linear regression and Cox modeling were used to evaluate outcomes. RESULTS: Median age was 60.3 years; 87% had KPS ≥ 70, 37.5% had gross total resection, and 90% received TMZ. Prior to RT, 56.4% (375/665) patients had a lymphocyte measurement < 1.0 × 1000 cells [K]/μL. Within 42 days of CRT, 81.7% (536/656) had a lymphocyte measurement < 1.0 K/μL, 37.8% (248/656) < 0.5 K/μL. 10.7% (58/544) patients developed grade 2 or higher neutropenia, 9.1% (50/547) patients developed grade 2 or higher thrombocytopenia. On multivariable analysis (MVA), older age (AHR1.03, p< 0.001), unmethylated MGMT status (AHR2.56, p< 0.001), lower RT dose (< 54Gy, AHR 3.45, p< 0.001), male sex (AHR1.45, p=0.02), non-gross total resection (AHR1.63, p< 0.001), lymphopenia during CRT (AHR0.63, p=0.008) and higher NLR during CRT (AHR1.02, p=0.001) were significantly associated with worse OS. Older age (AHR1.01, p=0.02), unmethylated MGMT status (AHR2.44, p< 0.001), lower RT dose (AHR1.82, p=0.02), higher NLR during CRT (AHR1.03, p < 0.001) were significantly associated with worse PFS on MVA. At first recurrence, median lymphocyte count was 0.7 K/μL with 74% (348/468) patients < 1.0 K/μL and 27% < 0.5 K/μL. CONCLUSION: Lymphopenia and higher neutrophil-to-lymphocyte ratio are associated with inferior outcomes. Persistent lymphopenia at time of first recurrence may have implications for clinical trial eligibility and immunotherapy approaches in recurrent GBM.